2018
DOI: 10.21454/rjaic.7518.251.nrm
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular monitoring: an update

Abstract: This review makes an advocacy for neuromuscular blockade monitoring during anaesthesia care, by: (i) describing the fundamental principles of the methods currently available, at the same time emphasizing quantitative recording measurements; (ii) describing the different ways in which muscles respond to the effect of neuromuscular blockade and their use in clinical practice; (iii) presenting results of different studies on timing and agents of neuromuscular block reversal, including a recommendation for sugamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…The most important factors for addressing the problems after neuromuscular blockade, such as residual neuromuscular block, recurarization, and consequent pulmonary complications, are monitoring of neuromuscular functions and administration of appropriate antagonists [ 26 ]. In the present survey, 79.3% reported that a neuromuscular monitoring device was available for clinical application at their hospital, which was similar to the rates reported in a 2010 Korean survey (available in operating room [OR]: 83.3%, available in hospital: 79.5%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important factors for addressing the problems after neuromuscular blockade, such as residual neuromuscular block, recurarization, and consequent pulmonary complications, are monitoring of neuromuscular functions and administration of appropriate antagonists [ 26 ]. In the present survey, 79.3% reported that a neuromuscular monitoring device was available for clinical application at their hospital, which was similar to the rates reported in a 2010 Korean survey (available in operating room [OR]: 83.3%, available in hospital: 79.5%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia allows the performing of surgical procedures in a rapid, safe, and pleasant manner, producing analgesia, absence of awareness, and adequate muscle relaxation when needed [ 1 , 2 , 3 ]. A critical aspect of perioperative anesthetic care is the maintenance of homeostasis, including hemodynamic stability, oxygenation, ventilation, and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, frequently used neuromuscular monitoring patterns are always criticized for their diverse shortcomings ( Table 1 ). Despite its universal utilization in clinical settings, ACC is susceptible to artifacts and will probably generate an overrated block degree [ 12 , 14 ]. A conventional ACC-based apparatus records the monaxial movement of the target muscle; therefore, signal quality relies heavily on the posture of the recording sites [ 15 ].…”
Section: Introductionmentioning
confidence: 99%